1997
DOI: 10.1080/001401397188233
|View full text |Cite
|
Sign up to set email alerts
|

The effects of 6 weeks training on the physical fitness of female recruits to the British army

Abstract: The purpose of this study was to evaluate the influence of British army recruit training on the physical fitness and strength of female recruits. A total of 73 females (aged 17-23 years) of a single intake of Women's Royal Army Corps (WRAC) recruits were tested at the beginning and end of their 6-week recruit training programme at the WRAC training centre, Guildford. The battery of tests comprised the maximal cycle time for a standard NATO test as an indirect method of determination of maximal oxygen intake (V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 10 publications
1
15
1
Order By: Relevance
“…The importance of FFM in lifting ability has been highlighted previously by Rayson (1996) who reported correlations between FFM and performance in a maximal box-lifting task (almost identical to the BL145 used in the present study) of r = 0.86, 0.64 and 0.62 for pooled, male and female data, respectively. Brock and Legg (1997) reported a 2.4% increase in FFM in female recruits, which compares to a surprisingly large 8.2% increase for females in response to the modi®ed BT in the present study. Knapik et al (1980) and Patton et al (1980) also 275 Resistance training gains in British Army recruits observed large increases in FFM of 5.9 and 6.1% for females after 7 weeks of BT in the US Army.…”
Section: Kinanthropometrycontrasting
confidence: 78%
See 3 more Smart Citations
“…The importance of FFM in lifting ability has been highlighted previously by Rayson (1996) who reported correlations between FFM and performance in a maximal box-lifting task (almost identical to the BL145 used in the present study) of r = 0.86, 0.64 and 0.62 for pooled, male and female data, respectively. Brock and Legg (1997) reported a 2.4% increase in FFM in female recruits, which compares to a surprisingly large 8.2% increase for females in response to the modi®ed BT in the present study. Knapik et al (1980) and Patton et al (1980) also 275 Resistance training gains in British Army recruits observed large increases in FFM of 5.9 and 6.1% for females after 7 weeks of BT in the US Army.…”
Section: Kinanthropometrycontrasting
confidence: 78%
“…The fact that both training programmes produced either marginal reductions or no change in isometric force production is probably the main conclusion to be drawn. Other data from British Army BT are those from Brock and Legg (1997) for females who also displayed no signi®cant change in isometric lift strength (UP), but did improve in incremental dynamic lift strength to a height of 1.52 m by 10.1% (compared with 15.5% when lifting to a height of 1.45 m in the present study). Legg and Duggan (1996) employed diVerent measures of muscular strength, and the ®ndings generally showed no consistent trend of increased strength that could be separated from physical maturation.…”
supporting
confidence: 43%
See 2 more Smart Citations
“…It is well known that basic training affects a variety of physiologic parameters like body mass index (BMI), skin folds, aerobic capacity, and muscular endurance. [7][8][9][10] Some studies have also measured changes in functional capacity during basic training 9,11 ; however, at present, it is not known whether the current military training program results in any enhancement in measures of functional capacity like intermittent endurance capacity and maximal jump performance. It also has not been fully elucidated to what extent development of overuse injuries is dependent on the initial physical fitness level of the individual.…”
Section: Introductionmentioning
confidence: 99%